(3GdcGaj aj GdbQGAGJ GdSHYs - (3CHh YHO Gddg eMeO Hf TQjM Hf CMeO GdQYjfj GdebQj GdfMhj GdGTHjdj,J (B476 (3g` s
(3ChdgG (B:s
(3bGd GdTjN Gdabjg GdCSJGP CHh GdMSf TQjM Hf eMeO Hf TQjM (B( (3V(B) (3bGd CHj GdMeO ddg Pi GdefI hGdWhd hGdbhI CeG HYO habc Gddg aEfi PGcQ ai gPG GdcJGH s
(3BNQgG (B:s
(3ShQI JHJ bQC YGUe MeGdI fUHkG hQaYgG GdHGbhf hdjS ajeG Hbi EdG eG PcQ s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdKGdKs
(3GdfSNI HgG MhGTs
(3Ydi ghGeTgG HYV GdJYdjbGJ s
(3hHgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
(3JHUQGJ GdCUd (B:s
Keywords: (3GdbQGAGJ hGdJLhjOs